Evaluating the Potential of Routine Blood Tests to Identify the Risk of Deep Vein Thrombosis: A 1-Year Monocenter Cohort Study. (August 2017) - Signorelli, Salvatore Santo; Valerio, Fiore; Davide, Castrogiovanni; Oliveri Conti, Gea; Maria, Fiore; Ignazio, Morana; Margherita, Ferrante
Study on 295 consecutive medical patients to evaluate the potential of routine blood tests to identify the risk of deep vein thrombosis (DVT). The tests included in a DVT risk stratification model system were erythrocyte sedimentation rate, antithrombin III, C-reactive protein, D-dimer, and N-terminal pro-brain natriuretic peptide. The DVT risk stratification system was moderately prognostic (area under the curve: 0.838; 95% confidence interval: 0.771-0.904; P < .001), whereas its performance was as follows—sensitivity, 100%; specificity, 20%; positive predictive value, 21%; and negative predictive value, 100%. The prevalence of DVT and DVT + superficial thrombophlebitis was 7.5% and 3.1%, respectively. These routine blood tests may prove helpful to stratify the DVT risk in medical patients.